A BRANCH-AND-PRICE APPROACH FOR THE TEAM ORIENTEERING PROBLEM WITH TIME WINDOWS - Tae, Hyunchul; Kim, Byung-In (International Journal of Industrial Engineering: Theory, Applications and Practice, 2015)